Utility of intracranial pressure monitoring in patients with traumatic brain injuries: a propensity score matching analysis of TQIP data. - Chopko, Ashley; Tian, Mingmei; L'Huillier, Joseph C.; Filipescu, Radu; Yu, Jinhee; Guo, Weidun A. (European Journal of Trauma & Emergency Surgery, 2024)
Purpose: Intracranial pressure monitoring (ICPM) is central to traumatic brain injury (TBI) management, but its utility is controversial. Methods: The 2016–2017 TQIP database was queried for isolated TBI. Patients with ICPM [(ICPM (+)] were propensity-score matched (PSM) to those without ICPM [ICPM (−)] and divided into three age groups by years (< 18, 18–54, ≥ 55). Results: PSM yielded 2125 patients in each group. Patients aged < 18 years had a higher survival probability (p = 0.013) and decreased mortality (p = 0.016) in the ICPM (+) group. Complications were higher and LOS was longer in ICPM (+) patients aged 18–54 years and ≥ 55 years, but not in patients aged < 18 years. Conclusions: ICPM (+) is associated with a survival benefit without an increase in complications in patents aged < 18 years. In patients aged ≥ 18 years, ICPM (+) is associated with more complications and longer LOS without a survival benefit.